Preparing an Online Dictionary of Business Communication: From Idea to Design - Sven Tarp (Lexikos, 2015)
This article discusses the plan for an online English–Spanish dictionary of business communication based on the function theory. After a short overview of lexicographical traditions within this field, it focuses on the philosophy behind the overall dictionary concept, the methods applied to develop this concept, some of the requirements for the corresponding database, as well as the foreseen Internet user interface which may lead the user to ten completely different articles for each word entered in the search field.